DOI: 10.11606/d.18.2008.tde-14062008-202738
|View full text |Cite
|
Sign up to set email alerts
|

Análise dos efeitos da borracha moída de pneu e do resíduo de óleo de xisto sobre algumas propriedades mecânicas de misturas asfáticas densas

Abstract: A Deus, pela sua infinita bondade, amor, incentivo, força e motivação para a realização desse trabalho. Especialmente à minha família. Meus pais, Deonila e Laurindo, por todo ensinamento, amor, dedicação e apoio durante todos os acontecimentos da minha vida, e, apesar da distância, foram incansáveis e inigualáveis no apoio e compreensão. Aos meus irmãos, Emerson e Rubiane, por todo incentivo, paciência e amizade sincera. Ao meu namorado Vinicius pelo seu amor, apoio, companheirismo, dedicação, compreensão, e p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…Samples with a reduction of 20°C are not statistically different from samples compacted at the temperature obtained through the viscosity test, as a p-value of 0.11 was obtained for the neat binder and 0.37 for samples with 2% of sun/lower oil. Pilati (2008) also observed that the mixtures composed of shale oil-modi/ied binder had lower stiffness than the mixture with neat binder. Also, the increase in the oil content from 7% to 14% resulted in considerable decreases in stiffness.…”
Section: Resilient Modulusmentioning
confidence: 82%
See 1 more Smart Citation
“…Samples with a reduction of 20°C are not statistically different from samples compacted at the temperature obtained through the viscosity test, as a p-value of 0.11 was obtained for the neat binder and 0.37 for samples with 2% of sun/lower oil. Pilati (2008) also observed that the mixtures composed of shale oil-modi/ied binder had lower stiffness than the mixture with neat binder. Also, the increase in the oil content from 7% to 14% resulted in considerable decreases in stiffness.…”
Section: Resilient Modulusmentioning
confidence: 82%
“…Among the organic additives, it is worth highlighting the use of oils. In Brazil, several studies (Pilati, 2008;Ribeiro, 2011;Lucena et al, 2016;Rodrigues et al, 2017;Portugal et al, 2017;Luz et al, 2019) have been conducted to analyze the in/luence of the addition of vegetable oils in asphalt binders and asphalt mixtures. Overall, these authors veri/ied that even though the oil addition leads to increased permanent deformation and reduces elastic recovery of asphalt binders, it enables decreases in temperatures mixing and compaction of asphalt mixtures, besides increasing storage stability and adhesion between aggregates and the asphalt binders.…”
Section: Introductionmentioning
confidence: 99%
“…Analisando a variavel do teor de óleo vegetal residual, o Módulo de Resiliência diminui à medida que aumenta a quantidade de óleo. Fato este que foi observado nos estudos de Pilati (2008) com óleo de xisto, Carvalho (2018) com óleo de girassol e Guerra (2019) com óleo de mamona.…”
Section: Análise E Discussão Dos Resultadosunclassified
“…Even when comparing the binder contents for HMA prepared with asphalt binders modified with SBS copolymer and asphalt-rubber binders, it is natural to expect slightly higher binder contents for the HMA prepared with asphalt-rubber binders (Pilati, 2008;Onofre, Castelo Branco, Soares, & Faxina, 2013;Domingos, 2017).…”
Section: Methods Proposed By Coutinho Et Al (2011) and Adapted By Frementioning
confidence: 99%